Mitochondrial haplogroup A is a genetic risk factor for atherothrombotic cerebral infarction in Japanese females - Nishigaki, Yutaka; Yamada, Yoshiji; Fuku, Noriyuki; Matsuo, Hitoshi; Segawa, Tomonori; Watanabe, Sachiro; Kato, Kimihiko; Yokoi, Kiyoshi; Yamaguchi, Sachiyo; Nozawa, Yoshinori; Tanaka, Masashi (Mitochondrion, 2007)
Mitochondrion-derived reactive oxygen species possibly play an important role in the pathogenesis of atherosclerosis and atherothrombotic cerebral infarction, because mitochondria in vascular endothelial cells are the major site of superoxide production. In the present study, we surveyed mitochondrial haplogroups associated with atherothrombotic cerebral infarction in 1081 Japanese subjects. Twenty-six mitochondrial single nucleotide polymorphisms of 11 major mitochondrial haplogroups (F, B, A, N9a, M7a, M7b, M7c, G1, G2, D4, and D5) were determined by use of 28-plex PCR and fluorescent beads combined with sequence-specific oligonucleotide probes. Multivariate logistic regression analysis with adjustment for conventional risk factors revealed that mitochondrial haplogroup A was associated with atherothrombotic cerebral infarction in female subjects (P< 0.05). However, no significant association was detected for males. Our study shows that haplogroup A confers an increased risk of atherothrombotic cerebral infarction in Japanese females. Validation of our findings will require additional studies with independent subject panels.